2016
DOI: 10.5194/acp-16-11083-2016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of particulate emissions from tropical biomass burning using a global aerosol model and long-term surface observations

Abstract: Abstract. We use the GLOMAP global aerosol model evaluated against observations of surface particulate matter (PM2.5) and aerosol optical depth (AOD) to better understand the impacts of biomass burning on tropical aerosol over the period 2003 to 2011. Previous studies report a large underestimation of AOD over regions impacted by tropical biomass burning, scaling particulate emissions from fire by up to a factor of 6 to enable the models to simulate observed AOD. To explore the uncertainty in emissions we use … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
128
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(141 citation statements)
references
References 132 publications
(174 reference statements)
13
128
0
Order By: Relevance
“…Scaling factors can range from 1.5 to 5, representing a significant underprediction of aerosol abundance in the atmospheric column. The EF values presented here are generally either similar to or lower than previous values reported for this biomass burning environment, suggesting that the EFs used in models are not responsible for the underestimate of AOD over tropical South America; several modelling studies have been undertaken during SAMBBA (Archer-Nicholls et al, 2015;Reddington et al, 2016;Pereira et al, 2016;Johnson et al, 2016) and have required scaling of their emissions to match in situ and satellite measurements. Consequently, scaling emission factors to match observations implies that the discrepancy lies elsewhere if it does relate to emissions (e.g.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Scaling factors can range from 1.5 to 5, representing a significant underprediction of aerosol abundance in the atmospheric column. The EF values presented here are generally either similar to or lower than previous values reported for this biomass burning environment, suggesting that the EFs used in models are not responsible for the underestimate of AOD over tropical South America; several modelling studies have been undertaken during SAMBBA (Archer-Nicholls et al, 2015;Reddington et al, 2016;Pereira et al, 2016;Johnson et al, 2016) and have required scaling of their emissions to match in situ and satellite measurements. Consequently, scaling emission factors to match observations implies that the discrepancy lies elsewhere if it does relate to emissions (e.g.…”
Section: Discussionmentioning
confidence: 63%
“…We recommend that comparisons of techniques be made in the future to assess the size of any such potential biases. Our calculated EFs do not indicate that the scaling of emissions that is required within global and regional numerical models to reproduce in situ and satellite aerosol concentrations over Brazil (Kaiser et al, 2012;Tosca et al, 2013;Archer-Nicholls et al, 2015;Reddington et al, 2016;Pereira et al, 2016;Johnson et al, 2016) is related to underestimates in EFs used in emission inventories.…”
Section: Discussionmentioning
confidence: 95%
“…Some recent inventories have started to use satellite retrievals of fire radiative power instead of burnt area which appears superior at least in some world regions (Kaiser et al, 2012). However, a comparison of five global biomass burning emission inventories based on different satellite fire or burned area products showed a large range of 365-1422 Tg CO emissions for the year 2003 (Stroppiana et al, 2010;Reddington et al, 2016). Different estimates of biomass burning emissions are also highly variable in the spatial patterns, temporal variability, and long-term trends (Schultz et al, 2008).…”
Section: Biomass Burning Emissionsmentioning
confidence: 99%
“…Our estimate for the integral emissions over the fire season considered is a factor of 2.2 larger than the corresponding estimate based on the GFED4 data. Based on comparison of satellite-derived and simulated AOD, several previous studies showed evidence that OC emissions provided by the GFED inventory may indeed be underestimated in different regions of world, including Siberia (see, e.g., Petrenko et al, 2012;10 Tosca et al, 2013;Konovalov et al, 2014;Reddington et al, 2016), although it was also argued (Konovalov et al, 2015;2017b) that models may underestimate AOD due to inadequate representations of the BB aerosol aging processes. So it is possible that a part of the differences between our optimal estimate of the OC emissions and the corresponding GFED data may compensate for some missing processes (e.g., involving the formation of SOA due to oxidation and condensation of semi-volatile organic compounds) in our model.…”
Section: Bc and Oc Emission Estimates 15mentioning
confidence: 99%
“…CC BY 4.0 License. Konovalov et al, 2014;Reddington et al, 2016). In this study, the MODIS AOD data were used to constrain OC emissions and to optimize the calculated AOD values.…”
Section: Introductionmentioning
confidence: 99%